EFFECT OF PRESTRESSING STRANDS ON THE LOAD DEFLECTION BEHAVIOR OF STEEL BEAMS - Shahada Mahmoud, Kamal; Mohammed Rasheed, Mohammed; Khalaf Mohaisen, Saad (Journal of Engineering and Sustainable Development, 2019)
Seven simply supported steel beams were tested to explain the effect of strengthening by external prestressing strands. All of these beams have the same steel section, clear span length and the strengthening samples implemented by two external prestressing strands. The tested beams are divided into two categories according to existing of external prestressing strands, the first category consists of one steel beam as a reference, while, the second group deals with steel beams strengthened by external prestressing strands and consists of six steel beams divided according to the eccentricity location of prestressing strand with jacking stress (814.589 MPa). During the test, it was found that the load-deflection curves for tested beams strengthening with external prestressing strand are stiffer as compared with the reference beams and the percentage of stiffening increases with increasing the eccentricity locations, while, the maximum load-deflection increase to 0.173%, 26.086%, 33.043%, 48.521%, 13.739% and 69.565 % with increasing the eccentricity location from (0 to 165) mm respectively as compared with the reference beam, on the other hand, the increasing percentage in deflection at mid-span decrease to -29.094%, -7.753%, -19.764%, 11.976%, -8.965% and -23.779% with increasing the eccentricity the location from (0 to 165) mm respectively as compared with the reference beam and the quarter span deflection to mid-span deflection ratio (δ quarter / δ mid) is bout (0.497).